Sosialisasi dan Pelatihan Pemanfaatan Biopestisida Mikroba Antagonis Campuran untuk Mengendalikan Penyakit Bawang Merah di Musim Hujan - Abdul Manan; Endang Mugiastuti; Loekas Soesanto (Universitas Mathla'ul Anwar Banten, 2021)
SOCIALIZATION AND TRAINING ON THE UTILIZATION OF MIXED ANTAGONISTIC MICROBIAL BIOPESTICIDES TO CONTROL SHALLOTS IN THE RAINY SEASON. The constraints on shallot cultivation in the rainy season are the more severe attacks of Fusarium oxysporum (Fusarium wilt) and Alternaria porii (purple disease). Solid formula of Trichoderma sp., Bacillus sp. B8, and Bacillus sp. B11 have been proven to increase their effectiveness and also cultivation technique and environmental modification. However, the benefit of the technology did not informed members of Farmers Group in Tambaksogra Village, Sumbang Regency, Banyumas District yet. The objectives of the activity are to increase farmers’ knowledge and skills on shallot cultivation technique out of the season, to multiply and to apply the antagonistic microbes solid mixed formula, to increase the crop production quantity and quality, and to increase farmers’ income. The method used was transfer of the technology through education, training, and demplot. The activities carried out were socialization of the potency and application of shallot cultivation technique out the season, multiplication and application of the antagonistic microbial solid mixed formula with the use of available media at the location, demonstration plot of the shallot cultivation technology with the application of the solid mixed formulation compared to single antagonistic, and farmers’ accompaniment in implementing the technology package. Result showed that there was an increase in farmers’ knowledge on the potency and application of solid formula biopesticides by 69.61%, as well as an increase skill in making solid formula biopesticide and its application by 64.33%.